Gaps in online education in the times of a pandemic in the opinion of Polish and Kenyan students - Babicka-Wirkus, Anna; Cywiński, Aleksander; Muoki Joshua, Stephen; Walat, Wojciech (Adult Education Discourses, 2022)
The authors aim to answer the research question: ‘What do you miss most about online education?’. The rationale for the research is that this form of education is likely to continue to be used. Referring to the quality strategy, the authors concentrate on the meaning of words used in responses to the above-mentioned open question, which was part of the research on the ‘Socio-technological aspects of academic education during the pandemic – from an international perspective’. The tool used was an electronic questionnaire, which was completed by 796 respondents from Poland, including 678 students and 118 academic teachers, as well as 41 students from Kenya. The questionnaire consisted of 31 closed and 6 open questions. The responses of Polish students and academic teachers, as well as Kenyan students, indicate the following categories: ‘contact’, ‘organisation’ and ‘technical dimension’. It forms an image of a specifically understood craft, work performed in separation, and the place of residence. The component in the form of modern technologies only modernises the educational process but does not make it satisfactory for either party of the aforementioned social relationship. The conclusion that can be drawn from the research is as follows: in the face of the COVID-19 pandemic, the primary task is to reorganise the contact between students and academic teachers in such a way that it is possible to achieve the assumed learning outcomes.